Assay of mycobacterium tuberculosis in biopsy specimens taken from hepatic granuloma patients using polymerase chain reaction method - İlyas TUNCER,; O. Kaya KÖKSALAN,; Kadir DEMİR,; Dinç DİNÇER,; Salih TÜRKOĞLU,; Sabahattin KAYMAKOĞLU,; Uğur ÇEVİKBAŞ,; Selim BADUR,; Atilla ÖKTEN,; Yılmaz ÇAKALOĞLU, (Turkish Journal of Gastroenterology, 2019)
-